2017
DOI: 10.5194/isprs-annals-iv-5-w1-1-2017
|View full text |Cite
|
Sign up to set email alerts
|

Bim and Gis: When Parametric Modeling Meets Geospatial Data

Abstract: ABSTRACT:Geospatial data have a crucial role in several projects related to infrastructures and land management. GIS software are able to perform advanced geospatial analyses, but they lack several instruments and tools for parametric modelling typically available in BIM. At the same time, BIM software designed for buildings have limited tools to handle geospatial data. As things stand at the moment, BIM and GIS could appear as complementary solutions, notwithstanding research work is currently under developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…Consequently, it provides a digital representation of architecture and the surrounding environment with different LoD options, but also serves as a bridge between remotely sensed data and terrestrially surveyed data. For example, once a 3D model (point cloud, mesh, and the Industry Foundation Classes (IFC)-format model) of the Multi-Door Stupa has been obtained, it could be integrated with the geospatial terrain, streets, and water data automatically retrieved from Autodesk InfraWorks' existing repositories (Figure 11), which include OpenStreetMap's buildings, highways, and railways, or orthophotos from BingMaps and DEM (e.g., United States Geological Survey (USGS) or Aster datasets) [41,42]. Terrestrially surveyed results such as CAD drawings, SketchUp models, and point clouds can also be georeferenced with the existing data.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it provides a digital representation of architecture and the surrounding environment with different LoD options, but also serves as a bridge between remotely sensed data and terrestrially surveyed data. For example, once a 3D model (point cloud, mesh, and the Industry Foundation Classes (IFC)-format model) of the Multi-Door Stupa has been obtained, it could be integrated with the geospatial terrain, streets, and water data automatically retrieved from Autodesk InfraWorks' existing repositories (Figure 11), which include OpenStreetMap's buildings, highways, and railways, or orthophotos from BingMaps and DEM (e.g., United States Geological Survey (USGS) or Aster datasets) [41,42]. Terrestrially surveyed results such as CAD drawings, SketchUp models, and point clouds can also be georeferenced with the existing data.…”
Section: Discussionmentioning
confidence: 99%
“…As a GIS tool can provide accurate information regarding vertical highway alignment, more accurate results can be produced as compared to the results that were generated by conventional methods. A previous study confirmed that an integrated BIM-GIS model is a powerful tool for simplifying and speeding up the planning and design process [39]. Geospatial information is important in infrastructure projects and the GIS model can perform geospatial analyses; however, the GIS model lacks the necessary instruments for parametric modelling that are available in BIM.…”
Section: Integrated Bim-gis Model In Highway Projectsmentioning
confidence: 92%
“…In fact, the accustomed syntactic approaches targeted to such integration do not allow a complete exchange of semantic and geometric information from BIM to GIS field and vice versa. It is worthy to point out the recent study on the 14 c. bridge across the Adda River at Lecco, which besides the elaboration of the HBIM themes of 3D survey and parametric modelling through NURBS , has developed the topic of linking BIM model and geospatial data useful in the infrastructure domain (Barazzetti and Banfi 2017). The relationship ifcOWL-CityGML is being further explored in several ongoing researches (Matrone et al 2019).…”
Section: Towards Semantic Interoperabilitymentioning
confidence: 99%